2012
DOI: 10.7314/apjcp.2012.13.2.427
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products for Cancer-Targeted Therapy: Citrus Flavonoids as Potent Chemopreventive Agents

Abstract: One example is hesperidin having the ability to decrease the concentration of serum and hepatic lipid and reduce osteoporosis of ovariectomized rats. Those studies showed the great potential of citrus fruits as natural product to be developed as not only the source of co-chemotherapeutic agents, but also phyto-estrogens. Therefore, further study needs to be conducted to explore the potential of citrus fruits in overcoming cancer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
135
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(151 citation statements)
references
References 59 publications
3
135
0
7
Order By: Relevance
“…Resistance to most of the available anticancer agents such as anthracyclines and taxanes, and its increasing incidence are the foremost obstacle in current breast cancer therapy (Valero and Hortobagyi, 2003;Lodha et al, 2011). This ultimately necessitates an unmet need for novel therapies of breast cancer yet in its advanced malignancy (Kviecinski et al, 2008;Meiyanto et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Resistance to most of the available anticancer agents such as anthracyclines and taxanes, and its increasing incidence are the foremost obstacle in current breast cancer therapy (Valero and Hortobagyi, 2003;Lodha et al, 2011). This ultimately necessitates an unmet need for novel therapies of breast cancer yet in its advanced malignancy (Kviecinski et al, 2008;Meiyanto et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Naringenin protective effects have been widely studied: antioxidant effects (Renugadevi and Prabu 2009), modulation of cytochrome P450 detoxification enzymes (Huong et al 2006), modulation of plasma cholesterol levels (Jeon et al 2007), and antihyperglycemic effects (Jung et al 2004) have been reported. In addition, several experimental data support anticarcinogenic and pro-apoptotic effects of Nar in numerous types of cancer (Arul and Subramanian 2013;Meiyanto et al 2012;Weng and Yen 2012). Most of these effects have been obtained by using variable Nar concentrations ranging from 1 to 100 lM.…”
Section: Introductionmentioning
confidence: 97%
“…Naturally occurring compounds in plants have been shown to inhibit multidrug resistance with minimal side effects (Cragg and Meiyanto et al, 2012). Furthermore, many existing FDA-approved anticancer agents are of natural origin (Saunders and Wallace, 2010).…”
Section: Introductionmentioning
confidence: 99%